MODEL TEAMS GAMES TOURNAMENT: Suatu Analisis Hasil Implementasi dalam Pembelajaran Pendidikan Agama Islam - Firmansyah, Mokh Iman; Tantowi, Yusuf Ali; Fawziah, Gina Ratnanisa (Universitas Pendidikan Indonesia, 2019)
Abstract. The effectiveness of a model can be seen from an indication of the increased quality of the process and learning outcomes. High or low student learning activities have an influence on the achievement of learning objectives that have been set. The preliminary study results showed the phenomenon of the low learning activities of class VII F students in PAI learning, especially in doing assignments and discussing in groups which of course must be solved immediately. Through the descriptive method with the CAR model, it is known that the alternative solution is to apply the teams games tournament (TGT) model. After going through two cycles of action and each cycle goes through the stages of planning, implementation, observation, and evaluation, showing the results that the application of the TGT learning model has become a trigger in increasing student learning activities in PAI learning. Students interested in getting involved in games and tournaments after previously taking steps in presenting and working with teams.Abstrak. Efektivitas suatu model terlihat dari indikasi meningkatnya kualitas proses dan hasil pembelajaran. Tinggi atau rendahnya aktivitas belajar siswa memiliki pengaruh terhadap tercapaianya tujuan pembelajaran yang telah ditetapkan. Hasil studi pendahuluan diketahui fenomena rendahnya aktivitas belajar siswa kelas VII F dalam pembelajaran PAI, terutama dalam mengerjakan tugas dan berdiskusi dalam kelompok yang tentunya harus segera dipecahkan. Melalui metode deskriptif dengan model PTK, diketahui bahwa alternatif pemecahannya adalah dengan menerapkan model teams games tournament (TGT). Setelah melalui dua tindakan siklus dan setiap siklusnya menempuh tahap perencanaan, pelaksanaan, observasi, dan evaluasi, menunjukkan hasil bahwa penerapan model pembelajaran TGT telah menjadi pemantik dalam meningkatkan aktivitas belajar siswa dalam pembelajaran PAI. Siswa mempunyai ketertarikan untuk terlibat dalam games dan tournament setelah sebelumnya menempuh langkah penyajian dan berkerja bersama tim.